Analisis Sistem Antrian Pada Masa Pasca Covid’19 Dengan Model Multi Channel-Multi Phase Dalam Optimalisasi Pelayanan Nasabah Bank BRI Unit Aek Kanopan (Labura) - Desrinawati Tindaon; Sudianto Manullang (Pusat Riset dan Inovasi Nasional, 2023)
Administrative and banking services at PT. Bank BRI Unit Aek Kanopan (Labura) has 2 services consisting of teller services and customer service services. Teller services and customer service services often experience queues of customers coming and making service transactions. This study aims to determine the optimal level of the queuing system for teller service and customer service with the help of C Sharp application. This study discusses the shape of the queuing model. The queuing model used is Multi Channel-Multi Phase with the control notation type (M/G/2)∶ (FIFO/∞/∞). The Multi Channel-Multi Phase model is a multi-stage multiple-line queuing system method. With a FIFO (First in first out) service pattern, namely first come first served earlier and earlier out. The results of this study are based on the results of calculating arrival patterns and service time patterns, there are 2 parts to the research results consisting of teller services and customer service services. In teller service, the average customer arrival (λ) is 1.48 customers per minute, the average customer that can be served (μ) is 5.12 customers that can be served per minute, and the average level of service intensity ( ρ) is 3.78 < 1. Furthermore, in customer service, the average customer who comes (λ) is 0.83 customers who come per minute, the average customer who can be served (μ) is 0.01035 customers that can be served per minute, and the average level of service intensity (ρ) is 0.015 < 1. Based on the results of the analysis of the queue system for teller service and customer service, it can be concluded that the optimal level of teller service and customer service can be said to be sufficient effective and optimal. In order to make the service more effective, add one service line or service facilities for both services.